Protection and enhancement of the historical and architectural heritage in times of peace on apparently distant war wounds. Some cases in Cagliari (Italy) between restorations, current problems and future prospects - Dessi, Maria; Fara, Emanuela; Piredda, Piervanna (Technical Annals, 2023)
The most recent conflicts in the European territory have focused the attention on the question of the protection of heritage after the war event, which now not appears in Italy as a distant problem, both temporally and geograph- ically. The study here proposed examines the case of the city of Cagliari, the regional capital of Sardinia (Italy), which is centrally located in the Mediterra- nean. The city appears to be an interesting and complete model due to the variety of cases that can be found here. It seems interesting how the typology of property has (or has not) often led to a reconstruction method. Historical cartography and images was compared with the current state; it is pos- sible to observe the results of the buildings reconstruction (or part of the building) or urban void generated, to identify the main unsolved problems. The problems generated by the Second World War bombings, were examined eighty years after the end of the conflict. We therefore want to understand what the approach to reconstruction in relation to the different intended uses of the assets and their architectural quality was, in the various decades, from the post- war period until today. Furthermore, it is interesting to examine whether the interventions were carried out in accordance with the regulations and / or with cultural indications that have followed, by comparing the local issue with the national one. This occasion ap- pears to be useful to reflect on the results of the damages of the city, where they remain severely compensable.